High commissioner Bristol’s implementation of Wilsonian internationalism in Asia minor and its shortcomings - Barton, Charles (Études sur la Région Méditerranéenne, 2020)
This article is an examination of the commonalities and incongruities between Woodrow Wilson’s liberal internationalism and the conduct of Admiral Mark Lambert Bristol, America’s High Commissioner in Turkey. The article uses both secondary and primary sources to investigate Bristol’s policies and statements. It focuses on his lack of concern for the plight of the Armenian and Greek communities in Asia Minor, and his efforts to support American businesses and protect them from restrictions placed by other Allied powers. The article finds that while Admiral Bristol failed to consider issues of justice for minority communities in Turkey, he did, in fact, seek to improve the likelihood of a democratic future for the region by pursuing the Open Door Policy, the internationalization of the Straits, while also attempting to counter European designs on the region. While his aims were aligned with Wilson’s desires, Bristol’s methods and callousness towards minority communities were not in keeping with Wilson’s vision.